Early-onset squamous cell carcinoma in xeroderma pigmentosum: A rare case - Susanto, Claudia; Paramita, Deryne Anggia (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Xeroderma pigmentosum (XP) is a rare autosomal recessive genodermatosis characterised by photosensitivity, dry skin, pigmentary abnormalities, premature skin aging, and skin cancers at an early age. This case report aims to alert health professionals about this disease, considering the rarity of the disease and the need for an early diagnosis of patients with XP. A 4-year-old boy was referred to our department with multiple painful ulcerated masses over his head and face, which had developed over the past two years. At the age of 6 months, the patient started to develop hyperpigmented spots of numerous sizes on his face, and gradually spread to the other sun-exposed areas of his body. He also had dry skin, photophobia, redness, and watery eyes. Dermatological examination showed multiple ulcerated erythematous nodules at the temporal and frontotemporal region; multiple scaly, hyperpigmented macules, papules, and cutaneous horns at the facial region; multiple hypopigmented and hyperpigmented macules, generalised distributed, predominantly over the sun-exposed areas. A biopsy examination from one of the nodules showed keratinising squamous cell carcinoma (SCC). The patient was diagnosed with xeroderma pigmentosum and was treated with multidisciplinary assessment involving dermatology, paediatric, oncology surgery, ophthalmology, and otolaryngology. The diagnosis in this patient is made clinically based on history taking, physical examination, and confirmation of malignancy from biopsy. Early diagnosis of XP is crucial for decreasing the development of neoplasms, which could improve the patient’s quality of life.